Improving Student Competence in the Preparation of Individual Teaching Programs for Students with Special Needs in Inclusive Classes - Ni’matuzahroh Ni’matuzahroh (Universitas Muhammadiyah Sidoarjo, 2016)
This research aimed to improve students’ ability in developing Individual Teaching Program (PPI) Module for Children with Special Need. This study used quasi experimental with between-group design. Seventh semester of Psychology students who was taking a Psychology for Children with Special Need course were the subject of the research. Data collection was obtained through observation, interview, Focus Group Discussion, and documentation. The data analysis was descriptive-quantitative. The analysis result was used to interpret the research findings. The findings showed that most of the subjects got more understanding after treatment. The study implies that in the future research, it is necessary to conduct sustainable guided program, intensive time table, and implementation of the program so that the subjects experience the real practice